2000
DOI: 10.1063/1.481231
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation spectroscopy of Ca+(C2H4)

Abstract: We have studied Ca ϩ ͑C 2 H 4 ͒ by photodissociation spectroscopy in a reflectron time-of-flight mass spectrometer over the spectral range 440-790 nm. Ca ϩ is the only photofragment observed. We find four absorption bands of the complex and assign them to metal-centered transitions correlating with excitation of Ca ϩ ͑3d and 4 p͒. Spectral assignment is supported by ab initio electronic structure calculations of the complex and isotope substitution experiments. Calculations find a weakly bound ground state equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The experimental apparatus and its application in mass-selected cluster photodissociation experiments has been previously described so only a brief overview will be given here. Weakly bound Al + (alkene) complexes are produced in the supersonic molecular beam expansion from a standard transverse laser vaporization source. The supersonic expansion is initiated by a gas pulse of mixed alkene (5% ethene, propene, or butene) in Ar carrier gas from a pulsed supersonic valve operated at a backing pressure of ∼40 psi.…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental apparatus and its application in mass-selected cluster photodissociation experiments has been previously described so only a brief overview will be given here. Weakly bound Al + (alkene) complexes are produced in the supersonic molecular beam expansion from a standard transverse laser vaporization source. The supersonic expansion is initiated by a gas pulse of mixed alkene (5% ethene, propene, or butene) in Ar carrier gas from a pulsed supersonic valve operated at a backing pressure of ∼40 psi.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…We have previously reported on the photodissociation spectroscopy of a series of light metal ionethene clusters, M + (C 2 H 4 ) with M = Mg, Ca, Zn, and Al. Each bimolecular complex is weakly bound in a C 2 v π -bonding geometry with the metal ion lying above the plane of the ethene ligand. For the group II metal ions (Mg, Ca, and Zn), the dominant absorption features correspond to metal-based excitations that correlate with the metal ion s − p resonance transitions. However, for Al + ethene the Al + (3s3p←3s 2 ) resonance lies at much higher energy (∼7.42 eV) and the metal-centered band is not accessible for excitation wavelengths >220 nm. Rather, the near UV absorption spectrum is dominated by photoinduced charge transfer to excited states of the complex that correlate asymptotically with Al(3s 2 3p) + C 2 H 4 + product channels …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a function of increasing cation size, these authors observed a red shift in their spectra, which they attributed to a gradual decrease in the binding energy of the metal ion in the first electronic excited state. Given the significance of calcium in biological systems, it is somewhat surprising that gas-phase complexes of Ca 2+ have received only limited spectroscopic study; , , however, there have also been studies of quite large Ca 2+ -containing complexes via collision-induced dissociation. Singly charged Ca + has been the subject of a quite intensive study, where the isolated 4s valence electron can provide convenient electronic transitions at accessible wavelengths. ,, Because both magnesium and calcium are biologically important metals, , studies of their spectra in different ligand environments provide an opportunity to identify the different geometries complexes may adopt and also to explore the possibility of developing spectroscopic markers for the metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Significant work has gone into investigating metal ion-hydrocarbon reaction mechanisms and energetics. [9][10][11][12][13][14][15][16][17] Recently, we extended this method to investigate the more strongly bound Mg ϩ -acetaldehyde complex. [6][7][8][9] We have used photodissociation spectroscopy to probe metal ion-hydrocarbon interactions in a series of weakly bound complexes of light metal ions with small alkanes and alkenes.…”
Section: Introductionmentioning
confidence: 99%